Basics Stahlbau - Hanses, Katrin (Basics, 2017)
At the beginning of one's architecture studies, there are many unknowns: what is really important? how do I brainstorm a design idea? how can this idea be depicted and ultimately implemented? BASICS is a series that imparts fundamental knowledge in compact individual volumes as well as in topical compendiums. It offers precise, step-by-step discussions, systematically covering the most important material pertaining to a given topic. Tailored to the needs of students, the series addresses all key subject areas, including design, architectural presentation, construction, professional practice, building services, landscape architecture, and urbanism.